Komedya de Baler - Almario, Virgilio S.; Yglopaz, Anna Maria M.; Kilates, Marne; Pleguezuelos, Fernando Ramos; National Historical Commission (Philippines) ([Manila] Pambansang Komisyon sa Kasaysayan ng Filipinas, 2012)
On history and development of Komedya de Baler, the first national theater group of the Philippines.
I. Isang presentasyon -- II. Comedia/Komedya noon -- III. Komedya de Baler ngayon -- IV. Bukas ng komedya -- Mga Tala -- Mga sanggunian.
Includes bibliographical references (page 123)
Text in English, Spanish, and Tagalog.
Keywords: Komedya de Baler -- History; Theater -- Philippines -- History